Fungsi Belajar Tari Srimpi Sangupati Gaya Kasunanan Bagi Penari di Keraton Surakarta - indah cahyasari (Gelar : Jurnal Seni Budaya, 2020)
Srimpi Sangupati dance has beauty which is visualized by smooth move and in flow. The Process of Srimpi Sangupati dance creation is created based on devotion to life experience, that is why Srimpi Sangupati dance is full of education value. This writing is for analyzing kinds of benefits in learning Srimpi Sangupati Dance in Kasunanan Style. This research analysis process uses qualitative approach. Qualitative descriptive research method is done by study book, observation and interview. The research result concludes that learning Srimpi Sangupati in Kasunanan Style has benefits for ethics education, social, religious and cognitive  source.